Performance evaluation and comparison of Westwood+, New Reno, and Vegas TCP congestion control. - Grieco, Luigi A.
TCP congestion control has been designed to ensure Internet stability along with fair and efficient allocation of the network bandwidth. During the last decade, many congestion control algorithms have been proposed to improve the classic Tahoe/Reno TCP congestion control. This paper aims at evaluating and comparing three control algorithms, which are Westwood+, New Reno and Vegas TCP, using both Ns-2 simulations and live Internet measurements. Simulation scenarios are carefully designed in order to investigate goodput, fairness and friendliness provided by each of the algorithms. Results show that Westwood+ TCP is friendly towards New Reno TCP and improves fairness in bandwidth allocation whereas Vegas TCP is fair but it is not able to grab its bandwidth share when coexisting with Reno or in the presence of reverse traffic because of its RTT-based congestion detection mechanism. Finally results show that Westwood+ remarkably improves utilization of wireless links that are affected by losses not due to congestion.